Towards high-resolution water isotope analysis in ice cores using laser ablation cavity ring-down spectroscopy - Malegiannaki, Eirini; Bohleber, Pascal; Zannoni, Daniele; Stremtan, Ciprian; Petteni, Agnese; Stenni, Barbara; Barbante, Carlo; Vinther, Bo M.; Gkinis, Vasileios (2024)
A new micro-destructive technique for high-resolution water isotope analysis of ice samples using a Laser Ablation (LA) system coupled with a Cavity Ring Down Spectrometer (CRDS) is presented. This method marks the first time water isotope analysis is conducted directly on the ice, bypassing the traditional steps of melting and vaporizing the ice sample, thanks to the direct transition of ice into water vapour through the laser ablation process. A nanosecond ArF laser ablation system (193 nm) with an integrated two-volume ablation chamber was successfully coupled to a CRDS analyzer, utilizing nitrogen as the carrier gas. The application goal is the use of LA-CRDS for ice core studies, so a method for preparing ice standard samples using liquid water isotope standards, widely used for ice core analysis, is introduced. The measurements were conducted in a discrete mode, by performing laser ablation raster scans of 4 mm × 4 mm areas, establishing a sampling resolution of 4 mm along an ice core's depth. The water vapour concentration reaching the CRDS analyzer as well as the quality of the water isotopic measurements of δ18O and δD were influenced by laser parameters, such as laser spot size, repetition rate, laser fluence, ablation time as well as by the flow rates of the carrier gas. After optimizing the experimental conditions for water vapour formation, three ice standards samples were analyzed for calibration purposes on the VSMOW-SLAP scale and a section of an ice core sample was also tested. Critical parameters influencing the precision and accuracy of water isotopic measurements were investigated, and isotopic fractionation phenomena were identified, pointing to essential considerations for the technique's further development.